Exploring Informal Corruption Through Local Wisdom in Community-Based Zakat Institutions - Galuh Adi Wijaya; Wheny Khristianto, Wheny Khristianto; Panca Oktawirani; Deni Pramono (Electronic Journal of Social and Political Sciences (E-SOSPOL), 2025)
Community-based zakat management is a critical component of Islamic welfare systems, grounded in participation, social trust, and local wisdom. However, such systems are not immune to informal corruption. This study investigates the forms and drivers of informal corruption in local zakat distribution and examines how local cultural norms may legitimize or mitigate such practices. Using a qualitative approach with a descriptive-analytical design, the research integrates literature review, discourse analysis, and case documentation in Putukrejo village. Findings reveal three major patterns of informal corruption: nepotistic distribution, discretionary deductions by zakat managers, and non-transparent reporting. These are legitimized through patron-client relationships, elite dominance, and uncritical local norms. The study argues for a hybrid governance model combining public deliberation, community-based transparency, and social auditing. Reinvigorating local wisdom as a form of ethical control aligned with Islamic public ethics is essential to establishing a more equitable, participatory, and accountable zakat governance framework.